Optimizing the Mobilization Performance of the Sat Intelkam Political Unit to Realize Safe and Orderly Village Elections in the Legal Area of ​​Kendal Police - Tubagus Atmoko (Tanggon Kosala, 2022)
The focus of research in this final project is the optimization of the performance of the Political Unit in the Inteligence and security unit to create safe and orderly pilkades in the Kendal Police jurisdiction. This research focus is considered important because the election of village chief is a democratic party that is most prone to friction in the community. Therefore, Satintelkam of Kendal Police seeks to optimize the performance of the Political Unit so that its implementation is in accordance with Perkabik No.3 of 2013 concerning Police Intelligence Gathering. This research aims to: (1) describe the performance of the Political Unit's mobilization to realize safe and orderly village chief election, (2) find and describe efforts to optimize the performance of the Political Unit's gathering to realize safe and orderly village chief election in Kendal Police jurisdiction. In the conceptual literature to analyze the above problems, several theories are used in this study, namely; Management theory, organizational resource theory and SWOT Analysis theory. While the concepts used as a theoretical basis, namely; the concepts of Optimization, Performance, Rallying, Political Unit, Intelligence and security unit, village chief election and Community Security and Order. In this research, a qualitative method with descriptive analysis is used to process data and field research to obtain data directly by participant-observation. Primary and secondary data sources, using data triangulation to obtain data validity. xviii The results of the findings during this study are (1) The performance of the Political Unit is still not optimal, the implementation of the mobilization has not been fully adjusted to Perkabik No.3 of 2013 concerning Intelligence Gathering, such as not checking the daily mutation book, not being orderly in administration, not involving the police intelligence unit in the implementation of the mobilization and the supervision and control system that has not been maximized. (2) Efforts to optimize the performance of Political Unit in gathering are hampered due to the limited ability of personnel competence, adjusting the qualifications of members in the field that are not implemented due to the limited number of personnel. The conclusions in this final project, (1) The performance of the Satintelkam Political Unit's mobilization is still lacking, the implementation of the mobilization must comply with Perkabik No.3 of 2013. (2) Efforts to optimize the performance of the Political Unit have not been carried out properly due to limitations in terms of quality and quantity of members, inadequate tools and administrative processes and supervisory control that are not optimal.